PELATIHAN PEMBUATAN PRODUK SIMPLISIA DAN ANALISA JAMU TRADISIONAL TERSTANDAR BAGI KADER POSYANDU WILAYAH PUSKESMAS KELURAHAN WAENA KOTA JAYAPURA - Puguh Sujarta; Septriyanto Dirgantara (LPPM Uncen, 2019)
The use of herbs fo treatment, especially the use of medicines that have been integrated into formal health services in Indonesia is still low compared to some other Asian countries. Papuan medicinal plants have superior characteristic that are different from other provinces in Indonesia. The usage of potential natural products as medicines for Papuan communities are selected by a good understanding of herbal medicine. The potential of biological acticity from natural resources provides a great opportunity to developing this program. In this case, the activities of the Community Engagement activities with the title Training Program to Produced of Crude Material for Herbs and Analyze of Traditional Medicine for Mothers in Waena Public Health of Jayapura City ; secondly practicing how to analyze the product of traditional medicine; the third produces an output in the form of local and national community engagement journals. The methods used in the implementation of this activity are lectures, simulations or demonstrations as well as the direct practice of manufacturing products from indigenous plant drugs Papua. The conclusion that tarticipants are very enthusiastic to follow the activity of service and can know the development the program, Based on the evaluation result indicates that the participants have satisfaction level is high when viewed from percentage of all aspect.Keywords: crude material, traditional medicine, analyze, public health